2008
DOI: 10.1007/s00134-008-1268-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of osteopontin are increased in SIRS and sepsis

Abstract: 45. SIRS/Sepsis: clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 37 publications
4
44
2
1
Order By: Relevance
“…In accordance with a recent report revealing elevated circulating levels of OPN in patients with bacterial sepsis predominantly suffering from pneumonia [10], we demonstrate elevated local and systemic levels of OPN during Klebsiella pneumonia in mice. OPN was released rapidly into the bronchoalveolar space upon infection of the airways with K. pneumoniae, where it contributed significantly to the early recruitment of neutrophils.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with a recent report revealing elevated circulating levels of OPN in patients with bacterial sepsis predominantly suffering from pneumonia [10], we demonstrate elevated local and systemic levels of OPN during Klebsiella pneumonia in mice. OPN was released rapidly into the bronchoalveolar space upon infection of the airways with K. pneumoniae, where it contributed significantly to the early recruitment of neutrophils.…”
Section: Discussionsupporting
confidence: 93%
“…Based on these pro-inflammatory functions, OPN is therefore considered as a pro-inflammatory molecule and have been well investigated in a wide range of chronic inflammatory diseases (17–20). In contrast to its chronic pathophysiological role, current literatures show inadequate evidence on its role in acute inflammatory diseases, even though a few studies were carried-out in non-sterile inflammatory disease conditions, like polymicrobial sepsis, and Pneumococcal pneumonia infections (28–30). Therefore, dealing with the elucidation of the role of OPN in sterile and acute inflammation will enhance our understanding towards implementing OPN as a novel therapeutic target in a wide range of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine concentrations on the other hand, showed the highest concentrations 1 day after injury and were lower, but still higher than in healthy reference knees, at later time-points after injury. Since OPN is known to have proinflammatory abilities 17,36,37 and SPARC correlated moderately to levels of pro-inflammatory cytokines in this study, we hypothesize that OPN and SPARC, normally not found in abundance in other tissues than bone, may cause prolonged inflammation in the acutely injured joint. Considering the increasing body of evidence suggesting that inflammation is involved in the OA process, and specifically post-traumatic OA development 34 , we suggest that this hypothesis should be further tested.…”
Section: Table IIImentioning
confidence: 93%